Life cycle cost assessments for military transatmospheric vehicles - Eisman, Mel, 1949-; Gonzales, Daniel R.; Rand eBooks (Santa Monica, CA : RAND, 1997)
Advanced technology and demonstration programs currently under way may ultimately lead to a transatmospheric reusable launch vehicle suitable for insertion into low earth orbit or for delivery of payloads to distant targets within minutes. While such a reusable vehicle may carry out military, civil, or commercial missions, this report focuses on military missions that a transatmospheric vehicle (TAV) might perform. It describes the differences between commercial uses and military missions in terms of objectives, maintainability, and response times--differences that would affect vehicle design. The report summarizes several military TAV design concepts, with emphasis on technical features. After describing cost ground rules and assumptions, and the unique methodology and rationale for estimating the costs of military TAVs, preliminary RDT&E and life cycle cost assessments on two of the military TAV design concepts are provided. The authors find that in the long term, an air-launched military TAV would be more cost-effective than a small expendable launch vehicle such as Pegasus.
"Project Air Force."
Includes bibliographical references (p. 45).
Also available on the internet via WWW in PDF format.
Keywords: Aerospace planes -- United States -- Design and construction -- Costs; Airplanes, Military -- United States -- Design and construction -- Costs; Astronautics, Military -- United States; Product life cycle; Electronic books